Medicinal Herbs – Boon for Modern Veterinary Therapeutics - Basak, Gourab; Malakar, Rupam; Sharma, Ambika; Bharti, Sanjay K.; Sharma, Barkha (International Journal of Bio-resource and Stress Management, 2020)
Rasayan Chikitsa (Herbal therapy) is an ancient process of Indian treatment. Ayurveda was the only way of treatment in the then periods. In the global perspective, American, Arabian and Chinese civilizations were found to prefer this technique. Medicinal plants are efficient in preventive, promotional and curative applications. These are also experts in fertility enhancement and immunomodulatory effects. As a result, gradually the modern pharmacological advancements have curved to utilise their benefits. Such traditional medicines although prove much effective at a lesser dose but their desirability seems to be limited. As, ‘old is gold’, though the herbal medicines are replacing the space dramatically. Because of curing, alleviating and preventing onset of diseases, phytotherapy in animal health care also possesses much desiring for its choice. In veterinary, medicines based on natural raw materials and folk remedies from plants are in practice. Though, it is generally preferred for prophylactic measures, also vividly used for therapeutic applications in cases of milder and chronic diseases, recurrent infections, ecto-endo parasitic infestations. However, in organic livestock production also, herbal applications are very beneficial in order to combat the battle with chemical toxicities. Thus, an enormous growth has been noticed in the recent past for their successful curative approaches, minimum complications, cost effectiveness and easy availability. Hence, herbal medicines should be promoted for the sake of animal wellbeing, better husbandry benefits and good public health.